The Policies and Practices of Good Governance in Indonesian Tourism: a Case Study in Malang, East Java - Ika Nurhayani; Sri Endah Tabiati; Aris Siswanti; Hamamah Hamamah (Institute of Research and Community Service, University of Brawijaya)
Good governance is a method to organize resources by involving the local community to participate and to supervise the development of the country. Good governance in tourism ensures that the industry can involve and benefit the local community. This paper aims to investigate the policies and practice of good governance in Indonesian tourism using the city of Malang in East Java as a case study. This is done by: (1) a study on the Regulation of the Major of Malang on the Master Plan of the Development of Regional Tourism no. 34 year 2014 and (2) field observations in the city of Malang. The research shows that the regulation has fulfilled six characteristics of good governance: participation, consensus oriented, equity and inclusiveness, effectiveness and efficiency, and accountability but fails to fulfill the three criteria of good governance: the rule of law, the transparency and the responsiveness. On the other hand, on the practices of the good governance, the city government lacks communication with the stakeholders and it is advisable that the city government set this forum in the near future to discuss the solutions to better tourism in Malang.Keywords: Good governance, tourism, Indonesia, Malang